2021
DOI: 10.1007/s00217-021-03841-8
|View full text |Cite
|
Sign up to set email alerts
|

How acetaldehyde reacts with low molecular weight phenolics in white and red wines

Abstract: Acetaldehyde is a key compound in determining wine color evolution and sensory properties. Major wine metabolites reactive to acetaldehyde are phenolic compounds, mainly flavan-3-ols and anthocyanins. Many studies have been conducted with the purpose of investigating acetaldehyde reactivity in model solutions, but very poor are the reports of its fate in real wines. By means of LC-HRESIMS and UV/Vis HPLC, red and white wines exposed to an excess of acetaldehyde were analyzed with a specific focus on low molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
4
8
0
Order By: Relevance
“…Vanillin index can be considered an indirect, inverse measure of the oxidative polymerization of flavanols via methyl methine bridge, since acetaldehyde [19], like vanillin [20], reacts with the C8 and C6 positions of the flavanol A ring. As reported, part of these reactions could involve anthocyanins [10]. Data on the evolution of the vanillin index supported this hypothesis (Figure 3).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Vanillin index can be considered an indirect, inverse measure of the oxidative polymerization of flavanols via methyl methine bridge, since acetaldehyde [19], like vanillin [20], reacts with the C8 and C6 positions of the flavanol A ring. As reported, part of these reactions could involve anthocyanins [10]. Data on the evolution of the vanillin index supported this hypothesis (Figure 3).…”
Section: Resultssupporting
confidence: 82%
“…Acetaldehyde is a highly reactive compound, and in wines it undergoes several reactions, including those with sulfur dioxide, with flavonoids thus altering wine pigments, with polymeric tannins and with several other nucleophiles. Although reactions in which acetaldehyde is involved are of paramount importance for wine characteristics such as color and tannins [10], there are no studies yet about the effect of acidification management on acetaldehyde, pigments, color and tannins and on their evolution over time.…”
Section: Introductionmentioning
confidence: 99%
“…coloured) at wine pH with wine age. The results confirmed the existence of bleachable pigments in PPM, which was supported by previous studies (Cheynier et al, 2006;Cucciniello et al, 2021;Laitila, 2021). Cucciniello et al (2021) found that some types of non-bleachable pigments in acidic conditions may release monomeric anthocyanins.…”
Section: Presence Of Bleachable Pigments and Their Trends During Ageingsupporting
confidence: 90%
“…The results confirmed the existence of bleachable pigments in PPM, which was supported by previous studies (Cheynier et al, 2006;Cucciniello et al, 2021;Laitila, 2021). Cucciniello et al (2021) found that some types of non-bleachable pigments in acidic conditions may release monomeric anthocyanins. For example, the formation of acetaldehyde-bridged polymeric pigments such as M3G-acetaldehyde-(epi) catechin dimers was reversible and could release M3G.…”
Section: Presence Of Bleachable Pigments and Their Trends During Ageingsupporting
confidence: 90%
See 1 more Smart Citation